1984
DOI: 10.7164/antibiotics.37.1687
|View full text |Cite
|
Sign up to set email alerts
|

The acetylation of 6'-amino group of amikacin by a new enzyme prepared from Serratia sp.

Abstract: It was found that Serratia marcescens 43, Serratia proteamaculans 48 and Serratia sp. 45, all of which were clinically isolated, produced a new type of aminoglycoside acetyltransferase which acetylated amikacin at the 6'-amino group. 1-N-[(S)-3-Amino-2-hydroxypropionyl]gentamicin B (HAPA-B, SCH 21420) and gentamicin C2 were hardly inactivated by the enzymes and had effective antimicrobial activities against these strains both in vitro and in vivo. This kind of aminoglycoside acetyltransferase should be classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Therefore, the active concentrations in vivo are probably higher than the MICs in vitro and may be different from one drug to another. Finally, it is possible that our strain of S. marcescens produces a 6'-aminoglycoside acetyltransferase (AAC 6') enzyme, which preferentially inactivates tobramycin and amikacin (10,17,22), even though the MICs for surviving bacteria (both in vitro and in vivo) were apparently identical to those for the parental Legett et al (14) studied the effect of different doses and the interval of administration of netilmicin and gentamicin on a murine model of Klebsiella pneumoniae thigh infection or pneumonia. The authors found no difference in activity between the two antibiotics, but there were no data available in this research concerning the in vitro time-kill curves.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the active concentrations in vivo are probably higher than the MICs in vitro and may be different from one drug to another. Finally, it is possible that our strain of S. marcescens produces a 6'-aminoglycoside acetyltransferase (AAC 6') enzyme, which preferentially inactivates tobramycin and amikacin (10,17,22), even though the MICs for surviving bacteria (both in vitro and in vivo) were apparently identical to those for the parental Legett et al (14) studied the effect of different doses and the interval of administration of netilmicin and gentamicin on a murine model of Klebsiella pneumoniae thigh infection or pneumonia. The authors found no difference in activity between the two antibiotics, but there were no data available in this research concerning the in vitro time-kill curves.…”
Section: Methodsmentioning
confidence: 99%